Household task demands for quiet and focused behavior facilitate performance by ADHD youth - Mendes, Camila Guimarães; Drummond, Adriana F.; Miranda, Débora M.; Costa, Danielle S.; Mancini, Marisa C. (Arquivos de Neuro-Psiquiatria, 2016)
This study evaluated the associations among symptoms of attention-deficit/hyperactivity disorder (ADHD) and of oppositional defiant disorder (ODD) in children and adolescents’ performance in household tasks and assistance provided by caregivers. Parents of children from 6 to 14 years old with ADHD (n = 67) were interviewed with the Children Helping Out: Responsibilities, Expectations, and Supports (CHORES) instrument. Significant correlations were found between symptoms of ODD and assistance in self-care tasks (r = −0.31; p = 0.01); symptoms of hyperactivity correlated with assistance in self-care (r = −0.30, p = 0.01); and family-care (r = −0.25, p = 0.04) tasks. Age was directly associated with the number of tasks performed by children and inversely related to the assistance provided by caregivers. A greater number of ODD symptoms resulted in more household assistance from caregivers. Characteristics of ODD symptoms, such as disobedience and hostility in the face of authority, may limit these children in accessing household tasks by their own initiative, requiring assistance from caregivers.
Keywords: environment; behavior; attention deficit disorder with hyperactivity; caregivers